Analysis of University Students' Digital Literacy Based on Five Dimensions of Digital Competence - Auliya Rusmayanti; Jun Anas'ash Ritonga; Nezifa Qhayummi Zahra; Mawaddah Rahmah; Nurdalilah Nurdalilah; Desniarti Desniarti (Jompa Research and Development, 2026)
Information in the digital space. Using a quantitative descriptive survey design, 30 active undergraduate students from various Indonesian universities were selected through purposive sampling. Data were collected via a 30-item questionnaire based on five digital literacy dimensions: information access, information management and processing, digital communication and collaboration, digital security and privacy, and critical thinking and digital ethics, measured on a five-point Likert scale. Validity testing using corrected item-total correlation showed all items exceeded the 0.30 threshold, while reliability testing yielded a Cronbach's Alpha of 0.968, indicating excellent internal consistency. Descriptive statistics (mean scores and percentages) revealed that students' digital literacy generally falls into the high to very high category. The highest grand means were found in digital communication and collaboration (4.26) and digital security and privacy (4.26), both very high, followed by critical thinking and digital ethics (4.23). Information access (4.18) and information management and processing (4.15) fell into the high category. These findings indicate that while students are proficient in digital communication, collaboration, and security, further strengthening is needed in evaluating information credibility, using academic reference tools, and understanding copyright and data ethics.